THERMAL PERFORMANCE OF RESIDENTIAL HAUSE USING GREEN ROOF BY UTILIZING THE PASSION FRUIT PLANTS (PASSIFLORA EDULIS) AS ROOF COVER - Suwaldi Mopangga; Mohamad Jahja; Dewa Gede Eka Setiawan; Mursalin Mursalin; Idawati Supu; Meilan Demulawa; Abdi Gunawan Djafar (Jambura Physics Journal, 2023)
Urbanization is the movement of people from villages to cities, this has caused an increase in population growth in urban areas resulting in increased demand for development which has reduced land for green spaces, green roofs are present as a farming concept amidst limited land in urban areas as well as assisting in passive cooling. The process of photosynthesis must play a role in roof shading. The selection of vegetation in the form of passion fruit vines as a roof covering material can spread up to 24 m, the object of research is a house in a housing complex by comparing two rooms, using a vegetation roof cover and without a vegetation roof cover, based on the results obtained a room with a vegetation roof cover experienced a decrease in temperature as the growth of vines covered the roof, the results obtained were a comparison between the two rooms, namely 0.1℃ in January, 1.1℃ in February and 2.6℃ in March when the peak temperature is during the day.